ROLE OF PROFESSIONAL DEVELOPMENT IN SUPPORTING IMPLEMENTATION OF THE MERDEKA CURRICULUMAT SMAS TUNAS BHAKTI PONTIANAK - Patricia, Putri Maria; Maria Patricia, Putri; Sahrawi; Hafis, Malikul (Journal of Language Teaching Lingustics and Literature, 2025)
This study investigates the role of professional development in supporting the implementation of the Merdeka Curriculum at SMAS Tunas Bhakti Pontianak. Using a qualitative case study approach, data were gathered through interviews with an English teacher and the Vice Principal for Curriculum, as well as classroom and training observations. Thematic analysis revealed that professional development improves teachers’ ability to design teaching tools, apply student-centered methods, and implement project-based learning. Participation in training and learning communities (Kombel) strengthened pedagogical skills and collaboration. Despite facing limited resources and time constraints, teachers showed increased readiness and adaptability in implementing the curriculum. The findings emphasize the importance of sustainable, relevant, and practical training programs to ensure successful curriculum implementation.